2010
DOI: 10.1002/ctpp.201010048
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the 2D Tokamak Edge Modelling Codes for Conditions of Detached Divertor Plasma

Abstract: The paper discusses verification of the ITER edge modelling code SOLPS 4.3 (B2-EIRENE). Results of the benchmark against SOLPS 5.0 are shown for standard JET test cases. Special two-point formulas are employed in SOLPS 4.3 to analyze the results of numerical simulations. The applied relations are exact in frame of the equations solved by the B2 code. This enables simultaneous check of the parallel momentum and energy balances and boundary conditions. Transition to divertor detachment is analyzed quantitatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…At the rollover and beyond in the ramp, the simulated particle flux densities are much closer no matter which neutral model is invoked. The reason for the difference in J sat at lower n u is still unclear, but similar behavior was reported from a comparison between SOLPS4.3 and SOLPS5.0 in [41].…”
Section: Edge2d-eirene/solps43 Comparisonsupporting
confidence: 70%
“…At the rollover and beyond in the ramp, the simulated particle flux densities are much closer no matter which neutral model is invoked. The reason for the difference in J sat at lower n u is still unclear, but similar behavior was reported from a comparison between SOLPS4.3 and SOLPS5.0 in [41].…”
Section: Edge2d-eirene/solps43 Comparisonsupporting
confidence: 70%
“…It is chosen to take the molecular dissociation energy as volumetric losses, although this is an overestimation of the real target power reduction. drift effects) [45,50] the momentum flux due to the anomalous particle transport. S mom denotes the sources of momentum (see [45] for details), found to be dominated by momentum transfer to neutrals.…”
Section: Discussionmentioning
confidence: 99%
“…Using the current conservation, the electric field contribution can be eliminated by introducing, amongst others, the static electron pressure. With x the poloidal direction and y the radial one, the following equation is derived (in steady state and in the absence of drift effects) [45,50]: and h x , h y and h z = 2πR the metric coefficients, √ g = h x h y h z the elementary cell volume, Γ visc m the viscous momentum flux and Γ anom m the momentum flux due to the anomalous particle transport. S mom denotes the sources of momentum (see [45] for details), found to be dominated by momentum transfer to neutrals.…”
Section: Appendix B Derivation Of the Equation For The Ion Currentmentioning
confidence: 99%
“…In the initial phase of our ITER JINTRAC simulation studies, we conducted a considerable benchmark between EDGE2D and SOLPS 4.3 [33], which showed that the SOL/divertor physics description was in agreement between the two codes [34] (see appendix B). Moreover, we have also significantly modified EDGE2D to model plasmas with He as the majority species.…”
Section: Introductionmentioning
confidence: 99%